1955
DOI: 10.1037/h0040292
|View full text |Cite
|
Sign up to set email alerts
|

Wishing with dice.

Abstract: Since 1943 a number of experimental papers have appeared dealing with an effect called "psychokinesis." In a typical experiment, one or more gaming dice were thrown, mechanically or otherwise, while S wished the dice to come to rest with certain faces or combinations of faces uppermost. Under some conditions, with certain Ss, the dice favored the desired faces to a statistically significant degree. The effect was found to persist after the introduction of safeguards, including the use of a motor-driven cage to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1962
1962
1979
1979

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…In the first and only positive results from the ASPR by Dale (1946), with an excess of hits reported, there was no significant change in scoring rate. On the other hand, in the study by McConnell et al (1955), a small but significant QD was reported although the total number of hits was within chance expectancy. In a number of studies, declines of one sort or another have been noted, but did not conform to the lawful decline.…”
Section: Later Dice Testsmentioning
confidence: 69%
See 3 more Smart Citations
“…In the first and only positive results from the ASPR by Dale (1946), with an excess of hits reported, there was no significant change in scoring rate. On the other hand, in the study by McConnell et al (1955), a small but significant QD was reported although the total number of hits was within chance expectancy. In a number of studies, declines of one sort or another have been noted, but did not conform to the lawful decline.…”
Section: Later Dice Testsmentioning
confidence: 69%
“…The score for the pooled data for this organized section was -26.3 hits for the 8,534 die throws Overlapping with the night tests, was the day series carried out in 1948-50 with photographic recording of 393 wishing 5s. The results by the criterion of target hits was entirely negative (McConnell et al, 1955). This study with the Duke dice machine was repeated by Dale and Woodruff in 1951-52 in a combined PK-ESP test with 108 5s and 62,208 dice readings and the results were insignificant with respect both to hits and declines (Murphy, 1952b).…”
Section: Later Dice Testsmentioning
confidence: 94%
See 2 more Smart Citations
“…To begin with something concrete: McConnell, Snowden, and Powell (1955) (Department of Biophysics, University of Pittsburgh) undertook to replicate a series of Duke University studies showing (a) excess of hits where wishing for the various die-faces, (b) decline effects. They used a motor driven cage which whirled dice against a system of internal baffles, and as the cage came to rest at the end of each 180° turn, automatically photographed them.…”
mentioning
confidence: 99%